URGENSI DEWAN PENGAWAS KOMISI PEMBERANTASAN KORUPSI (DEWAS KPK) MENURUT UNDANG-UNDANG NOMOR 19 TAHUN 2019 DAN FIQIH SIYASAH - Anggi Safitri; Siti Ngainnur Rohmah (Jurnal Penelitian Multidisiplin Ilmu, 2022)
Law Number 30 of 2002 concerning the Corruption Eradication Commission (KPK), as the first regulation that became the institutional basis for the Corruption Eradication Commission (KPK). Then, it was revised into Law No.19 of 2019. The issuance of the new KPK Law caught the attention of the public, the most highlighted thing in the amendment to the KPK Law was the presence of the Supervisory Board as a new organ in the Corruption Eradication Commission (KPK) institution. The birth of this new organ within the Corruption Eradication Commission (KPK) received pros and cons from the Indonesian people. The purpose of this study was to find out and understand the urgency of the Supervisory Board of the Corruption Eradication Commission (DEWAS KPK) according to Law No.19 of 2019 and the Urgency of the Supervisory Board of the Corruption Eradication Commission (DEWAS KPK) according to Fiqh Siyasah. This research was a literature research with a normative legal approach (normative juridical). Data collection techniques were carried out by collecting library materials from primary and secondary data sources, namely from writings, books, journals or other writings such as published legal expert opinions. The results of this study indicated that the urgency of the Supervisory Board of the Corruption Eradication Commission (DEWAS KPK) according to Law No.19 of 2019 is the authority of the Supervisory Board of the Corruption Eradication Commission (DEWAS KPK) in granting wiretapping, search, and/or confiscation permits. Furthermore, the appointment of members of the Supervisory Board of the Corruption Eradication Commission (DEWAS KPK) which are not in accordance with the ideals of the Pancasila Law. Then, the urgency of the Supervisory Board of the Corruption Eradication Commission (DEWAS KPK) according to Fiqh Siyasah which was narrowed down in Siyasah Duturiyah indicate that the Supervisory Board of the Corruption Eradication Commission (DEWAS KPK) is not needed because if there is a violation of the code of ethics by the Corruption Eradication Commission (KPK), it is enough to hold a trial as an effort the imposition of sanctions under the supervision of the Corruption Eradication Commission (KPK) which is supervised in amar ma'ruf nahi mungkar. In addition, the authority of the Supervisory Board of the Corruption Eradication Commission (DEWAS KPK) in granting wiretapping, search and/or confiscation permits is too broad thus it adds to the complexity of the bureaucracy and is feared that there will be intervention against the Corruption Eradication Commission (KPK) in carrying out the eradication of corruption. Whereas according to fiqh siyasah the rules are made to prevent negative things (Sad al-dzari'ah). Thus, both existing and amending laws and regulations must bring benefit to the people.